Overview Of Students' Knowledge Of State Senior High School 3 Luwu Regarding Sexually Transmitted Diseases In Larompong District, Luwu Regency - Munsir Ahyar; Shulhana Mokhtar; Mohammad Reza Zainal Abidin; Sri Vitayani; Arnie Isnaini Arfah (Sean Institute, 2024)
Sexually transmitted diseases (STDs) are an important health problem, especially among adolescents. who are vulnerable to risk due to lack of knowledge. The increase in the number of incident sexually transmitted diseases worldwide have been observed in the 15-24 age group. According to the World Health Organization (WHO) , more from One million infection infectious sexual diagnosed every day around the world. Teenagers is a transition period that requires special attention and protection. This study aims to identify the description of students' knowledge of SMA Negeri 3 Luwu regarding sexually transmitted diseases in Larompong District, Luwu Regency, including the definition, types, signs and symptoms , transmission methods, risk factors, complications, and prevention. This study uses method descriptive with approach cross-sectional . The results of the study showed that the level of knowledge students ( i ) vary, with a good understanding of the meaning, symptoms, and prevention of STDs, as well as sufficient understanding about types and complications of STDs, but there is still a lack of understanding of the modes of transmission and risk factors associated with STDs . In general general majority student ( i ) has sufficient knowledge until good , but Still there is a number of aspect necessary knowledge improved . These findings indicate the importance of more intensive outreach and a comprehensive educational approach to increase knowledge and change behavior. student ( i ) use lower incidence PMS.